The Role of Firms and Job Mobility in the Assimilation of Immigrants: Former Soviet Union Jews in Israel 1990-2019 - Jaime Arellano-Bover; Shmuel San (CESifo GmbH, 2024)
We study how job mobility, firms, and firm-ladder climbing can shape immigrants' labor market success. Our context is the mass migration of former Soviet Union Jews to Israel during the 1990s. Once in Israel, these immigrants faced none of the legal barriers that are typically posed by migration regulations around the world, offering a unique backdrop to study undistorted immigrants' job mobility and resulting unconstrained assimilation. Rich administrative data allows us to follow immigrants for up to three decades after arrival. Differential sorting across firms and differential pay-setting within firms both explain important shares of the initial immigrant-native wage gap and subsequent convergence dynamics. Moreover, immigrants are more mobile than natives and faster at climbing the firm ladder, even in the long term. As such, firm-to-firm mobility is a key driver of these immigrants' long-run prosperity. Lastly, we quantify a previously undocumented job utility gap when accounting for non-wage amenities, which exacerbates immigrant-native disparities based on pay alone.
Keywords: J31; J61; F22; 330; immigration; firms; job mobility; labor market assimilation